Block-iterative algorithms for solving convex feasibility problems in Hilbert and in Banach spaces - Aleyner, Arkady; Reich, Simeon (Journal of mathematical analysis and applications, 2008)
We establish convergence theorems for two different block-iterative methods for solving the problem of finding a point in the intersection of the fixed point sets of a finite number of nonexpansive mappings in Hilbert and in finite-dimensional Banach spaces, respectively.